Hebrews : a commentary - Johnson, Luke Timothy (London : Westminster John Knox Press, 2006)
Luke Timothy Johnson's Hebrews: A Commentary in the New Testament Library offers a thorough and careful commentary on the complicated book of Hebrews, showing its meaning within the context of ancient culture and the theological development of the early church. Written by one of the leading New Testament scholars of the present generation, this commentary offers remarkable insights into this challenging text's Hellenistic, Roman, and Jewish contexts.
Hebrews in the Christian tradition -- Hebrews as a first-century composition -- Language -- Literary form -- Symbolic world -- Argument -- The circumstances of composition -- Rhetorical situation -- Date -- Author -- The theological challenge of Hebrews -- Living God, living Word -- Mature teaching of the Christ -- The path of discipleship -- Commentary -- Prologue 1:1-4 -- Scripture proves that the Son is greater than the angels 1:5-14 -- Excursus 1: Why the angels? -- We cannot neglect so great a salvation 2:1-9 -- The Son and his brothers 2:10-18 -- The Son is greater than Moses 3:1-6 -- Warning against faithlessness 3:7-19 -- Excursus 2: The wilderness as paradigm -- The Sabbath rest of God 4:1-13 -- Jesus the great High Priest 4:14-5:10 -- Excursus 3: Suffering and the obedience of faith -- Exhortation to progress and perseverance 5:11-6-12 -- God secures the promise with an oath 6:13-20 -- Abraham and Melchizedek 7:1-10 -- Excursus 4: The mysterious Melchizedek -- The change of priesthood 7:11-19 -- The Son is an eternal High Priest 7:20-28 -- The Son is mediator of a New Covenant 8:1-6 -- The promise of a New Covenant 8:7-13 -- Excursus 5: Old and New Covenants -- The worship of the Old Covenant 9:1-10 -- Excursus 6: Sanctuaries material and ideal -- Christ's worship in heaven 9:11-28 -- The efficacy of Christ's priestly act 10:1-18 -- Exhortation to enter and not fall away 10:19-31 -- Memory of the past as encouragement for the future 10:32-39 -- The faith of the ancients 11:1-7 -- The faith of the patriarchs 11:8-22 -- The faith of Moses and the Israelites 11:23-31 -- The faith of many witnesses 11:32-40 -- Excursus 7: In praise of Israel's heroes -- Exhortation to join the pilgrimage of faith 12:1-17 -- Approaching the living God 12:18-29 -- Exhortation to faithful living in community 13:1-17 -- Final prayer and greeting 13:18-25.
Includes bibliographical references (pages xvii-xxviii) and indexes.
Keywords: Bible. -- Commentaries